Synthesis, structure and magnetic studies of lanthanide metal–organic frameworks (Ln–MOFs): Aqueous phase highly selective sensors for picric acid as well as the arsenic ion. (8th January 2018) - Raizada, Mukul; Sama, Farasha; Ashafaq, Mo; Shahid, M.; Khalid, Mohd; Ahmad, Musheer; Siddiqi, Zafar A.
Graphical abstract: The highly selective and sensing behaviour of a series of Ln–MOFs for picric acid (PA) as well as As(III) ions in aqueous medium with the lowest detection limit has been discovered. Magnetic studies ascertained the antiferromagnetic interactions between the Ln⋯Ln atoms while the sensing mechanism has been ascertained from spectral titrations, time decay and DFT studies. Abstract: A series of three lanthanide metal–organic frameworks (Ln–MOFs) consisting of a planar functionalized dicarboxylic acid was synthesized. The Ln–MOFs, with the composition [Ln3 (PDC)3 Cl3 (H2 O)] n [Ln = La (1 ), Nd (2 ) or Pr (3 ), PDCH2  = pyridine-2, 6-dicarboxylic acid], were characterized employing spectral, time resolved fluorescence, magnetic, single crystal X-ray and PXRD analysis. X-ray crystallography confirms that the structure of the Ln–MOFs is constructed by trinuclear (Ln3 ) units and the deprotonated PDC 2− ligand, which is simplified into a 3-c, uninodal net having the vab topology with the 10^3-point symbol. The variable temperature magnetic susceptibility data indicate that there are antiferromagnetic interactions between Ln III ⋯Ln III ions in2 and3 with Curie constants of 5.917 (2 ) and 5.231 (3 ) cm 3  K mol −1, Weiss constants −60.71 (2 ) and −48.43 (3 ) K, and zJ ′ values −0.98 (2 ) and −0.31 (3 ) cm −1 . The 3D polymers1 –3 are characterized as being highly selective, sensitive and discriminative dual chemosensors for picric acid (PA) and the arsenite (AsO3 3− ) ion in aqueous medium. The sensing pathways were investigated by spectral titrations, time decay and DFT (B3LYP/def2–SVP) studies. The lowest detection limit has been discovered for the La analogue towards the sensing of both PA and AsO3 3− {or As(III)} ions with ∼0.22 and ∼1.46 ppb, respectively. Such MOFs exhibiting bifunctional sensing behaviour for an explosive (PA) as well as toxic ion, As(III), in the aqueous phase are disclosed as the first lanthanide 3D polymers with the lowest detection limit known so far for the said analytes.